HISTORICAL VALUES AND LOCAL MATERIALS DURING THE OLD ORDER AND NEW ORDER PERIODS IN INDONESIAN HISTORY TEXTBOOKS (Analysis and Criticism of Indonesian History Textbooks Class XII Senior High School): NILAI SEJARAH DAN MATERI KELOKALAN MASA ORDE LAMA DAN ORDE BARU DALAM BUKU TEKS SEJARAH INDONESIA - sukardi; Hieronymus Purwanta; Kabib Sholeh; , Nur Syafarudin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Indonesian history textbooks have been published by the Ministry of Education and Culture from the curriculum of the old order, new order and post-reform periods, but the content in the textbooks still has not changed much in terms of data presentation despite many recent research results. Likewise, in terms of important historical value, writing has not been done in history textbooks. The purpose of this scientific work is to analyze historical materials in textbooks during the old order – new order and to analyze historical values in history textbooks as learning for students. The method used in this study uses qualitative methods, with a literature review approach through journals or history textbooks. Data analysis using qualitative discriptive. The results of this study reveal the criticism of historical material presented in the class XII high school Indonesian history textbook, published by the Ministry of Education and Culture in 2015. In matari analysis is still political, economic and government history whose studies are centered on Java and Jakarta. Regarding local material, the latest research results have also not been presented in textbooks. Historical values have also not been written in the textbook even though the purpose of students studying history is to study historical values for understanding the present and the future.